Identifying the key roles of a multicriteria framework for designing sustainable urban bridges in Ethiopia - Hailemariam, Leule M.; Nuramo, Denamo A. (Frontiers in Built Environment, 2022)
This research investigates the role of using a multicriteria framework during the process of designing a sustainable urban bridge. A framework is a basic structure underlying a system, concept, or method. It is a hypothetical depiction of a complex entity or process. A multicriteria framework, on the other hand, is a framework that comprises several criteria or attributes that relate to the widespread usage of difficult-to-understand ideas, concepts, and approaches. The general purpose of such a framework is to make it easier to apply sustainable urban bridge design for infrastructure improvement. The research uses a literature review and a questionnaire survey to identify the most key roles. The survey study using a structured questionnaire was applied to samples (n = 204) of practicing professionals in urban bridge infrastructure design. The principal component analysis was carried out to pinpoint the key components. As a result, the multicriteria framework predominantly addresses sustainability principles in design practice, and it also guides and facilities all bridge design processes from conceptual analysis to final design output.